DEPRESSION AND ITS SCREENING PROGRAMS AMONG VOLUNTARY AFRICAN MIGRANTS WITHIN AFRICA. A SYSTEMATIC REVIEW - Shallon Atuhaire; Nkechi Martina Odogwu, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Intra-continental migration has increased within Africa since the late 1980s. Africa to Africa migration ranks fifth globally. This study intended to review studies and document risk factors for depression, depressive symptoms, screening programs and coping strategies among voluntary African migrants within Africa. Online databases search was done to select journal articles published between 1980 and 2018 about the topic. PubMed generated only 8 relevant studies, Google Scholar 11, African Journals Online only 1 and international websites 3 relevant ones. Based on the keywords, Cochran protocol for quality assessment and PRISMA flowchart, 16 articles were systematically reviewed. Findings indicate few studies on depression among voluntary African migrants in Africa. Migration itself is a risk factor for depression. Other factors are trauma, poverty, forced or illegal migration, acculturation, loneliness, age, family separation, changing gender roles, and first-time migrants. It presents as insomnia, anxiety and social dysfunction. Most screening programs available are client initiated. Family support systems, problem-focused or emotions focused coping strategies can lessen depression. Conclusively, depression is a common scenario among migrants whether voluntary or involuntary but screening programs targeting voluntary migrants are very rare in most African settings. Culturally relevant and appropriate approaches targeting voluntary migrants would address the issue.